MILD Combustion: The Future for Lean and Clean Combustion Technology - M. M., Noor; Wandel, Andrew P.; Talal, Yusaf (Praise Worthy Prize S.r.l, 2014)
The future of today's society is greatly depending on the energy development. Due to the depletion of fossil fuel and the gradual development of energy generation from renewable sources, energy security becomes an important intergovernmental issue. This paper discusses the energy needs and the new combustion technology that will aid in achieving lean and clean combustion. In 2001, British Petroleum estimated the total natural gas reserves to be 187.5 trillion cubic meters, which can supply up to 7×1015 MJ of energy. The total petroleum reserves can supply up to 1,383 billion barrels which amounts to 8.4×1015 MJ of energy. Due to the increasing population and economic development, these fuel reserves will not last long. Energy efficiency and greenhouse gas emissions are two important and critical issues. The new combustion technology, moderate and intense low oxygen dilution (MILD) combustion provides a feasible solution. MILD, also known as flameless oxidation (FLOX) and high temperature air combustion (HiTAC) was discovered by Wünning in 1989. The thermal efficiency of combustion can be increased by about 30% and NOx emission reduced by 50%. MILD also can be achieved using different types of fuel such as gas fuel, liquid fuel and industrial waste fuel (saw dust). MILD combustion will be an important future combustion technology due to it producing higher efficiency and very low emissions.